An Innovative Approach towards Learners' Assessment of Instructional Process (LAIP) in an ODL Environment - Lim, Tick-Meng; Chiam , Chooi Chea; Norbaini Abdul Halim; Nur Azlin Omar; Phang, Siew-Nooi (2010)
Despite its popularity, the use SET in assessing teaching effectiveness for the purpose of appraisal has been controversial. This paper quantifies the weaknesses of the conventional evaluation of the instruction process and SET as a tool for assessing teaching. In this respect, this paper looks into the possibility of developing an innovative assessment tool named as the Learners' Assessment of Instructional Process (LAIP). This method is operationalised using various scoring matrices. The objective of LAIP is to offer an innovative alternative solution to assessment of instructional process in higher education institutions. Three factors have been identified as core determinants contributing to teaching and learning effectiveness, namely, knowledge, pedagogical skills and attitude. More specifically, LAIP is aimed at achieving the objectivity in the assessment of the instructional process in an ODL environment. (Authors' abstract)